Pengaruh Zakat, Infaq, dan Sedekah terhadap Indeks Pembangunan Manusia di Sumatera Barat - Kamarni, Neng; Saputra, Harsya; Aprilia, Cindy; Valerina, Citra (IQTISHODUNA, 2024)
This study analyzes the effect of Zakat, Infaq, Alms (ZIS) on the Human Development Index (IPM). The purpose of this study was to determine the effect of zakat, infaq and alms (ZIS) on life expectancy, the effect of zakat, infaq, and alms (ZIS) on years of schooling, the effect of zakat, infaq and alms (ZIS) on the expenditure of residents who is an indicator of the Human Development Index (IPM). The samples used in this study were 19 regencies/cities throughout West Sumatra Province from 2015 to 2022. This study used a quantitative analysis method with panel data regression. uses secondary data sourced from the West Sumatra National Amil Zakat Agency (BAZNAS). The findings in this study indicate that zakat, infaq and alms have a positive and significant effect on community education, zakat, infaq and alms have a positive and significant effect on public health, zakat, infaq and alms have a positive and significant effect on public spending where there is financial assistance social services can improve the quality of life of mustahik in West Sumatra.